KANDUNGAN DAN KELIMPAHAN MIKROPLASTIK PADA IKAN YANG DIDARATKAN DI PANTAI PASIR JAMBAK, PADANG - Yusra; Yempita Efendi; Sindy Gemaeka Putri; Lidya Dwi Handayani; Annisa Riski (JURNAL KATALISATOR, 2023)
The presence of microplastics is dangerous for fish and human health. The small size of microplastics (0.0001-0.5cm) makes it easier for microplastics to enter and accumulate in the bodies of living creatures. This research aims to analyze the shape, color and abundance of microplastics in fish landed at Pasir Jambak Beach, Padang City. The research was carried out in April - September 2023. Microplastic observations were carried out at the LLDIKTI X Laboratory using an Olympus CX21 microscope. The results of the research showed that the three types of fish landed, namely Mackerel fish (Rastrelliger neglectus), Lemuru fish (Sardinella lemuru) and Tongkol fish (Euthynnus affinis), were contaminated by microplastics. The total abundance of microplastics in three fish meats was 130 particles/g. The highest percentage of microplastic abundance was found in fiber microplastics with a percentage of 77% and the dominant color of microplastics was black.